Swelling effects on localized adhesion of an elastic ribbon. (1st May 2019) - Curatolo, M.; Nardinocchi, P.; Teresi, L.; Holmes, D. P.
Abstract : We investigate the adhesion mechanism between an elastic strip of vinylpolysiloxane bent in a racquet-like shape, and a thick elastomeric substrate with the aim to understand how local swelling modifies adhesion. Using a modified loop–tack adhesion test, we place a droplet of silicone oil in between the two materials, vary the dwell time and measure the force required to separate the two interfaces. The experiments are then compared with an analytical model that describes how the critical peel force is modified as the interfacial surface energy changes over time. Our study reveals that in certain circumstances swelling can enhance adhesion. More specifically, strong adhesion is obtained when most of the droplet is absorbed by the solid. By contrast, when the droplet remains at the interface a small adhesive force is measured.